Understanding the Attraction: Prison Tourism and the Public Gaze - Urquhart, Diane (The British journal of criminology, 2022)
Research undertaken in three decommissioned English prisons offers fresh insight into public attraction. Employing interviews with prison tourists, it reveals dark incentives rooted in historical and cultural representations of punishment, an inherent desire to look beyond the prison walls, and a fascination towards a concept I define as Abstract Death and Suffering.